Wong's nursing care of infants and children - Hockenberry, Marilyn J.; Wilson, David ;Rodgers, Cheryl C. (St. Louis, Missouri : Elsevier Science, 2019)
This edition features completely updated and reorganized chapters that present content in a clear, easy-to-understand way. New Quality Indicator boxes paint a bigger picture of hospitals and how they look at quality and safety. A focus on family-centered care emphasizes the role and influence of the family in health and illness with a separate chapter and Family-Centered Care boxes. Emergency Treatment boxes serve as a quick reference in critical situations. Pathophysiology Reviews explain complicated disease processes with illustrated summary boxes. Quality Patient Outcomes are discussed for major childhood diseases and disorders, showing how nursing care directly impacts patient outcomes. Nursing Tips include helpful hints and practical, clinical information.
Section I: Children, Their Families, and the Nurse -- 1. Perspectives of Pediatric Nursing -- 2. Social, Cultural, Religious, and Family Influences on Child Health Promotion -- 3. Hereditary Influences on Health Promotion of the Child and Family -- Section II: Childhood and Family Assessment -- 4. Communication, Physical, and Developmental Assessment of the Child and Family -- 5. Pain in Children: Significance, Assessment, and Management Strategies -- 6. Childhood Communicable and Infectious Diseases -- Section III: Family-Centered Care of the Newborn -- 7. Health Promotion of the Newborn and Family -- 8. Health Problems of the Newborn -- 9. The High-Risk Newborn and Family -- Section IV: Family-Centered Care of the Infant -- 10. Health Promotion of the Infant and Family -- 11. Health Problems of the Infant -- Section V: Family-Centered Care of the Toddler and Preschooler -- 12. Health Promotion of the Toddler and Family -- 13. Health Promotion of the Preschooler and Family -- 14. Health Problems of Early Childhood -- Section VI: Family-Centered Care of the School-Age Child -- 15. Health Promotion of the School-Age Child and Family -- 16. Health Problems of the School-Age Child -- Section VII: Family-Centered Care of the Adolescent -- 17. Health Promotion of the Adolescent and Family -- 18. Health Problems of the Adolescent -- Section VIII: Family-Centered Care of the Child with Special Needs -- 19. Impact of Chronic Illness, Disability, or End of Life Care for the Child and Family -- 20. The Child with Cognitive, Sensory, or Communication Impairment -- Section IX: The Child Who is Hospitalized -- 21. Family-Centered Care of the Child During Illness and Hospitalization -- 22. Pediatric Nursing Interventions and Skills -- Section X: Childhood Nutrition and Elimination Problems -- 23. The Child with Fluid and Electrolyte Imbalance -- 24. The Child with Renal Dysfunction -- 25. The Child with Gastrointestinal Dysfunction -- Section XI: Childhood Oxygenation Problems -- 26. The Child with Respiratory Dysfunction -- Section XII: Childhood Blood Production and Circulation Problems -- 27. The Child with Cardiovascular Dysfunction -- 28. The Child with Hematologic or Immunologic Dysfunction -- Section XIII: Childhood Regulatory Problems -- 29. The Child with Cancer -- 30. The Child with Cerebral Dysfunction -- 31. The Child with Endocrine Dysfunction -- Section XIV: Childhood Physical Mobility Problems -- 32. The Child with Integumentary Dysfunction -- 33. The Child with Musculoskeletal or Articular Dysfunction -- 34. The Child with Neuromuscular or Muscular Dysfunction.
Includes bibliographical references.
Keywords: PEDIATRIC NURSING